Factor Analysis Of Financial Literacy, Business Capital And Survival Strategies On The Sustainability Of Umkm During The Covid 19 Pandemic In Ketapang District - Abd. Mubaraq; Diah Arminingsih; Nur Atiqah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
A UMKM in West Kalimantan account for 98% of the total number of businesses in West Kalimantan. UMKM is the smallest level of business, namely micro business with a percentage reaching 81%. The Trade Sector such as Retail, Repair, Maintenance of Cars and Motorcycles has around 138 thousand UMKM businesses or reaching 47%. The Drinking Food Provision sector amounted to 62 thousand businesses reaching 21%. In Ketapang Regency, UMKM business actors are also one of the drivers of the economy. This study is to determine the partial and simultaneous effects of financial literacy variables, business capital, and survival strategies on the sustainability of UMKM businesses in Ketapang Regency. The results of this study indicate that the financial literacy and survival strategy variables partially have a positive and significant effect on the sustainability of UMKM businesses, and the business capital variable partially has a positive and insignificant effect on the sustainability of UMKM businesses. Also, simultaneously the variables of financial literacy, business capital, and survival strategies have a significant effect on the sustainability of UMKM businesses.